Kinect-sensor-controlled game for early diagnosis of visual problems. - Nemeth, Robert; Szucs, Veronika; Sik-Lanyi, Cecilia (International Journal of Child Health & Human Development, 2018)
The serious game was designed for early (preschool aged) vision-test at home or kindergartens. It was created with Windows Presentation Foundation (WPF) framework. This framework is a good choice to develop vision-test game modules, so they can be easily accessed from one main application. Our game module is a "Drag and Drop" game, which can be controlled with Kinect v2 sensor. The game is designed to take various objects along the tracks to the suitable finish. This type of game will help the user discover the visual acuity problems. The game monitors that how long it takes to complete the track with different difficulty settings. The results are stored.